EDUKASI GIZI DAN DEMONSTRASI MASAK CAMILAN LOKAL MOBIYU UNTUK PENCEGAHAN OVERWEIGHT DAN OBESITAS DI DESA SUKARAMI - Apri Maulana; Bunga Cyntia Bella; Nafisah Shakira; Siti Wulandari; Alya Putri Difa; Richa Pranita; Arcellia Nauvalinda; Maria Desmonda Fabiani; Revia Najwa Fitriani; Adnania Zikri Aulia; Ririn Artike Cahyani; Veni Apriliani; Devieka Rhama Dhanny (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2026)
The problem of excess nutrition, such as overweight and obesity, is a major concern in Sukarami Village due to the high incidence and its association with non-communicable diseases. This study aims to evaluate the effectiveness of nutrition education interventions and MOBIYU local snack cooking demonstrations in improving nutritional knowledge and perceptions of healthy snacks. The research method used a quantitative approach with a pre-experimental one group pretest-posttest design. Respondents were housewives who were selected purposively. The intervention was carried out once in the form of counseling and cooking practice. Data were collected through questionnaires before and after the intervention, Subsequently, the data were analyzed using univariate analysis to describe the characteristics of each variable individually. The results showed a increase in nutritional knowledge and positive perceptions of local healthy snacks. The local food-based approach has proven to be applicable and potential as a promotive effort to prevent obesity, although further evaluation is needed for the development of a more sustainable and equitable program.